Analýza daňového dopadu švarcsystému - Fišara, Vladimír (Vysoké učení technické v Brně. Fakulta podnikatelská, 2025)
Tato bakalářská práce se zabývá analýzou daňového dopadu tzv. švarcsystému, tedy nelegální formou výkonu závislé práce v prostřednictvím živnostenského oprávnění. Cílem práce je porovnat daňové zatížení zaměstnanců a osob samostatně výdělečně činných v situacích, které vykazují znaky závislé práce. V teoretické části jsou popsány základní pojmy, které souvisí se zastřeným pracovním poměrem. V analytické části jsou vypočteny jednotlivé příklady prokazující rozdílné zdanění zaměstnanců a podnikatelů, a také byla provedena krátká analýza firemních výkazů související se švarcsystémem. Na konci práce jsou uvedeny konkrétní návrhy opatření, které by mohly zmírnit užívání švarcsystému v České republice.

This bachelor´s thesis analyses the tax impact of the pseudo self-emlpoyment, an illegal form of disguised employment in which dependent work is carried out under a trade licence. The aim of the thesis is to compare the tax burden of employees and self-employed individuals in situations that exhibit characteristics of dependent work. The theoretical part explains basic terms related to disguised employment realtionships. The analytical part includes calculations of examples which show the difference between taxation employees and self-employed, as well as a brief analysis of companies financial reports connected to pseudo self-employent. At the end of the thesis are mentionted particular proposals aimed to reducing the use of bogus self-employment in the Czech republic.
Analysis of Tax Impact False Self-employment
Keywords: švarcsystém; OSVČ; zaměstnanec; zaměstnavatel; daň; příjem; sociální pojištění; zdravotní pojištění; pseudo self-employmnet; self-employed; employee; employer; tax; income; social security; health insurance